Sequence Analysis of the Cytochrome C Oxidase Subunit I Gene of Pseudagrion pilidorsum (Odonata: Coenagrionidae) - Tallei, Trina Ekawati; Koneri, Roni; Kolondam, Beivy Jonathan (Makara Journal of Science, 2017)
Pseudagrion pilidorsumis1of over 140 species of Pseudagrion (in thefamily Coenagrionidae), the largest genus of damselfly. This species exhibits dimorphism due to the different body colorations of males and females, making them difficult to distinguish from other congeneric species. This study analyzed thecytochrome C oxidase subunit I (COI) gene sequence of P.pilidorsum found in Bogani Nani Wartabone National Park (North Sulawesi) and compared it with other sequences of P. pilidorsum from distinct geographical locations in Asia. The COI gene for the Sulawesi specimen was amplified using the universal primer pair LCO1490 and HCO2198. A sequence homology search was conducted through BLAST. Multiple sequence alignment was executed using CLUSTALO (1.2.1). A phylogenetic tree was constructed using the Neighbor-Joining method, and genetic distance was calculated using the Kimura 2-parameter. The COI gene sequence of the Sulawesi specimen lies in the range of 83.99-89.10% with other P. pilidorsum deposited at Gen Bank, namely KF369526 (Sarawakspecimen), AB708543, AB708544, and AB708545 (Japan specimens). The genetic distance falls in the range of 0.146-0.149 between the Sarawak specimen and the Japan specimen; 0.122-0.125 between the Sulawesi and Japan specimens; and 0.185 between the Sulawesi specimen and the Sarawak specimen. It can thus be inferred that the Sarawak and Japan specimens may not belong to the same species; the Sulawesi and Japan specimens may not belong to the same species; and the Sarawak specimen and Sulawesi specimens might be placed in different genera.